Simulation and Analysis of AODV and DYMO Protocols under CBR in Wireless Sensor Network using Qualnet - Radhey, N; Nandal, V (International Journal of Computer Sciences and Engineering, 2025)
One of the major challenges in wireless CBR network is the design of roboust routing protocols .Routing protocol are designed to establish correct and efficient path between source and destination. .Wireless sensor is considered the best technology for the study of the performance parameters. MANET is self configured .All MANETs in wireless is connected through wireless link. AODV and DYMO are made to establish a correct relation between the sender and the receiver. Many protocols have been discovered in last few years. These are two of them. They have different property under the different application. Constant bit rate is used here to define the AODV and DYMO Protocols. In this paper, present the two mobile CBR network routing protocol, i.e. CBR on (AODV), CBR on (DYMO) . The performance analysis is done on the basis of network metric such as End to End delay, Average (jitter), total packet received and throughput.